2015
DOI: 10.1021/acs.joc.5b01055
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of Triostin A Using a Symmetrical Bis(diphenylmethyl) Linker System

Abstract: Triostin A is a symmetric bicyclic depsipeptide with very potent antitumoral activity because of its bisintercalation into DNA. In this study, we report a new synthetic strategy that exploits a structural symmetry of triostin A. First, we prepared a novel symmetric linker molecule that is labile under mildly acidic conditions and suitable for a solidphase synthesis procedure. Two Cys units were attached to a linker-resin conjugate via their free thiol groups, and double deprotection and double coupling reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…However, cyclization of the H-shaped intermediate was expected to form two isomers, 24 and 24a , possessing theta- and manacle-shaped rings, respectively . It has previously been reported that both theta- and manacle-shaped isomers of TA were obtained by a double cyclization of an H-shaped intermediate in a solid phase procedure . In the study, double cyclization between N -Me-Cys and N -Me-Val afforded an unnatural conformer of TA.…”
Section: Resultsmentioning
confidence: 99%
“…However, cyclization of the H-shaped intermediate was expected to form two isomers, 24 and 24a , possessing theta- and manacle-shaped rings, respectively . It has previously been reported that both theta- and manacle-shaped isomers of TA were obtained by a double cyclization of an H-shaped intermediate in a solid phase procedure . In the study, double cyclization between N -Me-Cys and N -Me-Val afforded an unnatural conformer of TA.…”
Section: Resultsmentioning
confidence: 99%
“…The structural characteristic of 1 is the thioacetal bridge within the macrocycle, and the total chemical synthesis of 1 has not yet been accomplished presumably because the difficulty in the chemical synthesis of 1 may lie with constructing the thioacetal moiety. Accordingly, synthetic studies have mainly been focused on 2 . Here, we describe the first total synthesis of 1 .…”
mentioning
confidence: 99%
“…Under these conditions, the diastereomer of 1 was also obtained in a yield of 4%; hence, the substitution of the chloro group by the methylthio group proceeded in a stereoselective manner. Triostin A ( 2 ) is a synthetically more accessible compound, and several total syntheses have been reported. Direct conversion of the disulfide moiety of 2 to the corresponding sulfide leading to 4 by treatment of 2 with P­(NEt 2 ) 3 with various temperatures and solvents was also investigated . However, these efforts were unsuccessful and 4 was not obtained at all.…”
mentioning
confidence: 99%
“…have potent activity in inhibiting the platelet-derived growth factor (PDGF) signaling pathway as well as an anti-biofilm activity. The synthesis skyllamycins AÀ C began with anchoring the linear peptide precursor onto a Sieber amide resin (104). Notably, the β-OHÀ Leu, β-OHÀ Phe, and β-OHÀ O-MeÀ Tyr were protected as oxazolidines to facilitate the macrocyclization.…”
Section: Cyclic Depsipeptidesmentioning
confidence: 99%
“…The synthesis of triostin A was achieved via anchoring the sulfur atoms of two N ‐Me‐Cys residues onto a symmetrical bis(diphenylmethyl) linker ( 181 ) (Scheme 27). [104] Then the chain was symmetrically elongated toward both of the two N ‐termini before biscyclization to give the resin‐bound bis‐macrocycle 183 . Finally, cleavage from the resin followed by oxidative disulfide bond formation generated triostin A ( 185 ).…”
Section: Solid‐phase Total Synthesis Of Cyclic Peptidesmentioning
confidence: 99%